Morphological and genetic variation in populations of Desmos chinensis Lour. (Annonaceae) - Isna Arofatun Nikmah; RUGAYAH RUGAYAH; Tatik Chikmawati (Society for Indonesian Biodiversity, 2021)
Abstract. Nikmah IA, Rugayah R, Chikmawati T. 2021. Morphological and genetic variation in populations of Desmos chinensis Lour. (Annonaceae). Biodiversitas 22: 811-822. Desmos chinensis is a woody climber or scandent shrub genus in Annonaceae that has moniliform fruits. Desmos chinensis Lour. can be found throughout Southeast Asia. This species is widely used as a traditional medicine in several countries in Asia, however, the information on its morphological and genetic variation has never been reported. The objective of this study was to reveal the genetic variation of Desmos chinensis on Java island (Indonesia) based on the morphological characters and Inter-Simple Sequence Repeats (ISSR) markers. Leaf samples were collected by exploring seven regions in Java island. Variation in morphological characteristics were described and discussed in detail. Genetic variation was assessed using the ISSR marker. The morphological characteristics of D. chinensis in Java varies in habit; leaf shape, leaf size, leaf color; flower position, flower reflexity, pedicel bract position, number of petals, petal color, petal shape, petal apex, undulation of petal; and number of monocarp per fruit. A total of 53 samples collected from seven populations were screened by 25 ISSR primers, wherein 11 primers produced 47 clear and reproducible bands covering 85.1% of polymorphic bands. Desmos chinensis in Java were divided into five natural populations. Furthermore, the mean value of the Shannon index and genetic diversity index were 0.223 and 0.151, respectively. Moreover, the variations within and among populations examined using AMOVA showed the occurrence of 38% of total genetic variations among the different populations, therefore, the remaining 62% was due to variations within the population. Morphological and genetic variations are important preliminary information for determining the conservation strategy of Desmos chinensis.